The The Riau Islands Province Arts Building in Tanjungpinang City - Fajar Noer Kholis (Journal of Aesthetics, Creativity and Art Management, 2023)
The activities of art actors in Tanjungpinang City are not well developed because they are not supported by the existence of supporting art activity facilities. This study aims to plan and design the Riau Islands Province Arts Building in Tanjungpinang which can accommodate various forms of art in it. The theme "Malay Stage" (Panggung Melayu) with the concept of Post-Modern Architecture, namely the Metaphor to Natural and Cultural approach can be used as a solution in responding to the problems that occur. This approach focuses on designing forms by analyzing the surrounding nature and culture today. The design of this arts building uses a qualitative descriptive research method, namely design by research. The use of Malay ornamentation and the choice of roof shape bring the historical atmosphere of Malay buildings to the present. Balanced with the use of building facade materials and roof parts by giving a neutral and bold color creates the impression of modernism in the building and can be used to organize art activities for the people of the Riau Islands Province. This study has resulted in the plan and design of the “Riau Islands Province Arts Building in Tanjungpinang”, which is hoped to become a medium for all kinds of Malay art forms in it. The theme "Malay Stage" with the concept of Postmodern Architecture used in this study is considered appropriate to be used as a solution in responding to problems that occur in the Riau Islands, especially in the aspect of preserving Malay arts and culture.